Mesoporous SBA-15 silica modified with calix[4]arene and β-cyclodextrin - Kuchma, O.V.; Zub, Yu.L.; Dabrowski, A.; Solcova, O. (Functional Materials, 2007)
Mesoporous SBA-15 type silica with covalently fixed β-cyclodextrin (0.56 mmol/g) and calix[4]arene (0.40 mmol/g) functional groups and with specific surface areas of 384 to 723 m²/g have been obtained.